Thermal bonding sheet and thermal bonding sheet with dicing tape

By designing an adhesion layer with a specific particle size distribution in the heating bonding sheet, the problem of poor dispersion of organic binder in the adhesion layer is solved, the adhesion strength between the semiconductor wafer and the sintered precursor layer is improved, and the stability of the manufacturing process is ensured.

CN120511228APending Publication Date: 2025-08-19NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510145660.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-19
Filing Date
2025-02-10
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

The dispersion of the organic binder in the adhesive layer of the conventional heating bonding sheet is poor, resulting in easy peeling between the semiconductor wafer and the sintered precursor layer, affecting the manufacturing process of the semiconductor device.

Method used

A heating bonding sheet is designed, including a sintered precursor layer containing sintered particles and an adhesion layer overlapping on one side. The content of sintered particles in the adhesion layer is 5 volume % or more and 40 volume % or less, and the particle size distribution has at least 2 peak apexes, so that the dispersion and uniformity of the particles are improved by the design of the particle size distribution.

Benefits of technology

The bonding strength between the semiconductor wafer and the sintered precursor layer is improved, the peeling phenomenon is reduced, and the manufacturing process of the semiconductor device is smooth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120511228A_ABST
    Figure CN120511228A_ABST
Patent Text Reader

Abstract

The invention provides a thermal bonding sheet and a thermal bonding sheet with a dicing tape. [Problem] To provide a thermal bonding sheet provided with an adhesion layer in which an organic binder has good dispersibility. [Solution] Provided is a thermal bonding sheet which is provided with a sintering precursor layer that contains sinterable particles and an adhesion layer that overlaps one surface of the sintering precursor layer, the adhesion layer containing an organic binder and sinterable particles, the content of the sinterable particles in the adhesion layer being 5-40 vol%, and the thickness of the adhesion layer being 10-30 [mu] m <-1 > / [mu] m <-1 > / [mu] m <-1 > / [mu] m <-1 > / [mu] m <-1 > / [mu] m <-1 > / [mu] m <-1 > / [mu] m. The particle size distribution of the sinterable particles contained in the adhesion layer has at least two peak points when the particle size distribution is measured.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims the benefit of Japanese Patent Application No. 2024-023094, which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a thermal bonding sheet and a thermal bonding sheet with a dicing tape used, for example, in manufacturing a semiconductor device. Background Art

[0004] Thermal bonding sheets used in the manufacture of semiconductor devices are conventionally known. Such thermal bonding sheets include at least a sintering precursor layer containing sinterable particles. The sintering precursor layer has pressure-sensitive adhesive properties due to, for example, containing an organic binder.

[0005] The sintering precursor layer is placed between one side of a substrate and a semiconductor element (semiconductor chip, etc.) during the manufacture of a semiconductor device and sintered to bond the substrate and the semiconductor element.

[0006] (1) After a sintering precursor layer is stacked on the adhesive layer of a dicing tape formed by laminating a base material layer and an adhesive layer, a semiconductor wafer is further attached to cut the sintering precursor layer and the semiconductor wafer into small pieces.

[0007] (2) Using a jig such as a collet, the small piece of the sintering precursor layer attached to one semiconductor element is peeled off from the adhesive layer, and the semiconductor element with the small piece of the sintering precursor layer attached is picked up.

[0008] (3) One semiconductor element having the small piece of the sintered precursor layer bonded thereto is bonded to one surface of the substrate (semiconductor element mounting region). In other words, one semiconductor element is temporarily fixed to the substrate.

[0009] (4) By repeating the above steps (2) and (3) a plurality of times, a plurality of semiconductor elements each having a sintered precursor layer bonded thereto are temporarily fixed to the semiconductor element mounting region of the substrate, thereby obtaining an intermediate product of a semiconductor device.

[0010] (5) A sintering treatment is performed by heating the intermediate semiconductor device product at a temperature at which the sinterable particles in the sintering precursor layer can sinter together, thereby sintering the sinterable particles and causing at least a portion of the organic binder to disappear from the sintering precursor layer. As a result, the plurality of semiconductor elements are bonded to the semiconductor element mounting region of the substrate.

[0011] After undergoing the various steps described above, the plurality of semiconductor elements are fixed to the semiconductor element mounting region of the substrate by sintering the sinterable particles contained in the sintering precursor layer. In other words, the plurality of semiconductor elements are fixed to the semiconductor element mounting region of the substrate by means of the sintered small pieces of the sintering precursor layer.

[0012] It should be noted that in the manufacture of semiconductor devices, the following processes can sometimes be performed instead of implementing the above-mentioned processes (1) and (2): a process of cutting only the semiconductor wafer into small pieces into multiple semiconductor elements after only sticking and fixing the semiconductor wafer on the adhesive layer of the dicing tape; a process of using a clamp such as a collet to peel and lift up a semiconductor element from the adhesive layer, and then pressing the semiconductor element onto the sintered precursor layer of the heating bonding sheet; a process of using the pressing force to cut a part of the sintered precursor layer into small pieces so that the size becomes equivalent to the size of the semiconductor element, and at the same time, bonding the small pieces of the sintered precursor layer to the semiconductor element; and a process of picking up a semiconductor element with a small piece of the sintered precursor layer bonded thereto by lifting a clamp such as a collet.

[0013] As a thermal bonding sheet that can be used in the above-mentioned semiconductor device manufacturing method, for example, a sheet including a sintering precursor layer that forms a strong sintered layer after sintering and an adhesion layer that is bonded to a semiconductor wafer or the like is known (for example, Patent Document 1).

[0014] Specifically, in the thermal bonding sheet described in Patent Document 1, the sintering precursor layer contains metal fine particles and an organic binder, and the adhesion layer contains, for example, metal fine particles and an organic binder.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent Document 1: Japanese Patent Application Publication No. 2018-037548 Summary of the Invention

[0018] Problems to be solved by the invention

[0019] However, the organic binder in the adhesive layer described in Patent Document 1 may not always have good dispersibility. If the organic binder in the adhesive layer has poor dispersibility, for example, when the sintered precursor layer and the semiconductor wafer are cut into small pieces on a dicing tape, the semiconductor wafer and the sintered precursor layer may peel off. More specifically, the two adherends (the sintered precursor layer and the semiconductor wafer) attached to the opposite sides of the adhesive layer may peel off.

[0020] However, it can be said that sufficient research has not yet been conducted on sheets for thermal bonding that include an adhesive layer having a well-dispersible organic binder.

[0021] Therefore, an object of the present application is to provide a sheet for thermal bonding including an adhesion layer having a good dispersibility of an organic binder.

[0022] Solutions for solving problems

[0023] In order to solve the above-mentioned problems, the thermal bonding sheet of the present application comprises: a sintering precursor layer containing sinterable particles; and an adhesion layer superimposed on one surface of the sintering precursor layer.

[0024] The adhesion layer contains an organic binder and sinterable particles, and the content of the sinterable particles in the adhesion layer is 5% by volume or more and 40% by volume or less.

[0025] The sinterable particles contained in the adhesion layer have at least two peaks in their particle size distribution when the particle size distribution is measured.

[0026] The thermal bonding sheet with a dicing tape described in the present application includes the thermal bonding sheet described above and a dicing tape superimposed on one surface of the thermal bonding sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1A This is a schematic cross-sectional view of the sheet for thermal bonding according to the present embodiment cut along the thickness direction.

[0028] Figure 1B This is a schematic cross-sectional view of the thermal bonding sheet with a dicing tape according to the present embodiment cut along the thickness direction.

[0029] Figure 2A This is a schematic cross-sectional view showing a state in which a semiconductor wafer is superimposed on a thermal bonding sheet with a dicing tape.

[0030] Figure 2B This is a schematic cross-sectional view showing an example of a situation in which a semiconductor wafer and a sheet for thermal bonding are cut into pieces.

[0031] Figure 2C This is a schematic cross-sectional view showing how a semiconductor chip and a small piece of the thermal bonding sheet are lifted from a dicing tape using a collet.

[0032] Figure 2D This is a schematic cross-sectional view showing a state in which a fragile region is formed inside a semiconductor wafer superimposed on a thermal bonding sheet with a dicing tape.

[0033] Figure 2E This is a schematic cross-sectional view showing another example of how a semiconductor wafer and a sheet for thermal bonding are cut into pieces.

[0034] Figure 3AThis is a schematic cross-sectional view showing a state in which a semiconductor chip having a small piece of a thermal bonding sheet attached thereto is temporarily fixed to a substrate.

[0035] Figure 3B This is a schematic cross-sectional view showing a state in which another semiconductor chip to which the small piece for thermal bonding sheet is attached is temporarily fixed to the substrate.

[0036] Figure 3C This is a schematic cross-sectional view showing an example of a state in which a small piece of the heat-bonding sheet is heated while being pressed.

[0037] Figure 4 This is a diagram showing a specific example of a particle size distribution chart obtained by measuring the particle size distribution of sinterable particles contained in the adhesion layer.

[0038] Figure 5 This is a photograph showing an example of an ultrasonic flaw detection image of a sheet for thermal bonding.

[0039] Description of Reference Numerals

[0040] 10: Heating and bonding sheet,

[0041] 1: Adhesion layer, 2: Sintering precursor layer, 3: Component migration prevention layer,

[0042] 100: Heating bonding sheet with dicing tape,

[0043] 20: Cutting tape, 21: Base material layer, 22: Adhesive layer,

[0044] A: Collet, X: Semiconductor chip,

[0045] D: Ceramic insulating layer, E: Copper die pad, F: Copper thin layer, H: Substrate. DETAILED DESCRIPTION

[0046] Hereinafter, one embodiment of the thermal bonding sheet according to the present application will be described with reference to the drawings.

[0047] In the heat bonding sheet 10 according to this embodiment, for example Figure 1A As shown, the sintering precursor layer 2 includes sinterable particles, and the adhesion layer 1 includes sinterable particles and is superimposed on one surface of the sintering precursor layer 2 .

[0048] In the heat bonding sheet 10 according to this embodiment, for example, Figure 1A As shown in FIG, the component migration prevention layer 3 containing at least a resin may be further provided. The component migration prevention layer 3 is, for example, overlapped with the dicing tape 20 (see FIG. Figure 1B ) is used as the adhesive layer 22.

[0049] The sheet 10 for thermal bonding of the present embodiment is, for example, in the form of a long strip and can be stored in a state of being wound into a cylindrical shape.

[0050] First, the sintering precursor layer 2 , which is the main layer of the thermal bonding sheet 10 according to the present embodiment, will be described in detail.

[0051] [Sintering Precursor Layer of Heating Bonding Sheet]

[0052] The sintering precursor layer 2 contains at least sinterable particles and preferably further contains an organic binder.

[0053] The sintering precursor layer 2 contains an organic binder and thus has pressure-sensitive adhesive properties. Therefore, the sintering precursor layer 2 can withstand a pressing force and temporarily bond an adherend.

[0054] In addition, if the sintering precursor layer 2 is subjected to a sintering process, the sinterable particles inside are sintered to each other. The sintering precursor layer 2 can be bonded to each other by, for example, being arranged between the substrate and the semiconductor chip X and undergoing a sintering process. If the sintering precursor layer 2 is subjected to a sintering process, at least a portion of the organic binder will disappear. The organic binder in the sintering precursor layer 2 preferably does not remain substantially after the sintering process, and more preferably does not remain at all.

[0055] The sintered particles contain a conductive metal. The conductive metal has an electrical conductivity of 100 [μS / cm] or more (10 6 [S / m] or more).

[0056] Examples of the conductive metal include gold, silver, copper, palladium, tin, and nickel. The conductive metal may be an alloy of two or more metals selected from the group consisting of gold, silver, copper, palladium, tin, and nickel. The sinterable particles may contain metal oxides such as silver oxide, copper oxide, palladium oxide, and tin oxide.

[0057] In this embodiment, the sinterable particles preferably contain at least one selected from the group consisting of silver, copper, silver oxide, and copper oxide. Thus, the semiconductor element can be more effectively bonded to the substrate using the small pieces of thermal bonding sheet 10 (small pieces 10' of thermal bonding sheet).

[0058] The sinterable particles preferably contain at least one of silver and copper as a conductive metal. This further improves the thermal conductivity and electrical conductivity of the sintered precursor layer 2.

[0059] The sinterable particles preferably contain silver as the conductive metal. By including silver in the sinterable particles, the oxidation resistance of the particles is improved, allowing for suitable sintering even in an air atmosphere. Specifically, for example, sintering can be suitably performed in an air atmosphere when bonding a semiconductor element such as a semiconductor chip X to a substrate. On the other hand, if the sinterable particles contain copper, for example, the sintering process can be performed in an inert atmosphere such as nitrogen to prevent oxidation of the copper.

[0060] The sinterable particles may contain a metal oxide. For example, the surface layer of the sinterable particles may be a state where the metal has been converted into a metal oxide.

[0061] For example, the sinterable particles may have a core-shell structure comprising a core portion and a shell portion covering the core portion. The core portion may contain at least one of silver and copper as a main component. The shell portion may contain gold, silver, silver oxide, or copper oxide as a main component. For example, the sinterable particles may have at least a portion of the surface of the silver particles covered with silver oxide, or at least a portion of the surface of the copper particles covered with copper oxide.

[0062] The particles formed of multiple metals may be particles having, for example, a core portion formed of nickel, copper, silver, aluminum, or the like and a shell portion formed of gold, silver, copper, or the like covering at least a portion of the surface of the core portion.

[0063] Furthermore, examples of sinterable particles include composite particles containing a metal and a material other than a metal. Examples of composite particles include particles having a core portion formed of resin particles and a surface portion, wherein the core portion is formed of a metal such as nickel or gold and covers at least a portion of the surface of the core portion. The core portion can be formed of a carbon material such as carbon black or carbon nanotubes. It should be noted that composite particles can be obtained by surface-treating metal particles with a fatty acid.

[0064] When the sinterable particles contain silver, more specifically, when the sinterable particles are silver particles, the silver particles may contain silver and other elements (such as metal elements) as unavoidable impurities. Alternatively, the silver particles may be surface treated (e.g., silane coupling treatment). Examples of surface treatment agents for the silver particles include fatty acid-based coating agents, amine-based coating agents, and epoxy-based coating agents.

[0065] Silver particles that have been surface-treated with a coating agent (hereinafter sometimes referred to as coating agent-treated silver particles) are preferred from the following perspectives. By using coating agent-treated silver particles as sinterable particles, the affinity between the organic binder and the sinterable particles can be further improved in the sintering precursor layer 2 before sintering. This allows the sinterable particles to be more fully dispersed in the sintering precursor layer 2 before sintering.

[0066] In the manufacture of the semiconductor device, as will be described later, by subjecting the sintering precursor layer 2 to a sintering treatment at a temperature equal to or higher than a predetermined temperature, at least a portion of the organic binder disappears from the sintering precursor layer 2 .

[0067] In addition, as the above-mentioned sinterable particles, only one type may be used, or two or more types may be used in combination.

[0068] The shape of the sinterable particles is, for example, needle-like, filamentous, spherical, or plate-like (including scaly) shapes, etc. Among these shapes, a spherical shape is preferred.

[0069] By making the sinterable particles spherical, the sinterable particles can be dispersed more satisfactorily in the varnish for obtaining the sintering precursor layer 2 described later.

[0070] The sinterable particles are sintered together by a sintering process in which the particles are heated to a predetermined temperature. The sinterable particles are particles in which at least a portion of each particle is formed from the conductive metal and are fixed to each other when heated at a predetermined temperature. Therefore, a heat transfer path is formed within the sintered precursor layer 2 after the sintering process. In particular, a heat transfer path is formed in the thickness direction. This allows the thermal conductivity (exothermicity) of the sintered precursor layer 2 to be increased after the sintering process.

[0071] The sinterable particles may be capable of sintering at a heating temperature of 400° C. or lower. In other words, sinterable particles in which necking is observed on the outer surface when heated at a temperature of 400° C. or lower may be used.

[0072] The temperature at which the sinterable particles sinter can be measured using a thermogravimetric differential thermal analyzer.

[0073] Specifically, a thermogravimetric differential thermal analyzer (e.g., Rigaku Corporation's TG8120 differential thermal balance) was used for measurement under the following conditions. This measurement yielded a Tg curve and a DTA curve. The temperature of the maximum DTA curve peak observed near the point of decline in the Tg curve was defined as the sintering temperature of the sinterable particles.

[0074] <Measurement Conditions>

[0075] Heating rate: 10℃ / min

[0076] ·Measurement atmosphere: Air

[0077] ·Measurement temperature range: room temperature (23±2℃)~500℃

[0078] Note that sinterable particles containing gold, silver, copper, palladium, tin, nickel, and alloys thereof as conductive metals can be sintered at a heating temperature of 400° C. or lower.

[0079] The average particle size of the sinterable particles is preferably 1 nm or larger, more preferably 10 nm or larger, and even more preferably 50 nm or larger. This improves the dispersibility of the sinterable particles in the varnish used to form the sintered precursor layer 2 described later. Therefore, the varnish can be used to form a sintered precursor layer 2 in which the sinterable particles are well dispersed.

[0080] On the other hand, the average particle size of the sinterable particles is preferably 10,000 nm or less, more preferably 3,000 nm or less, further preferably 1,000 nm or less, and even more preferably 500 nm or less. This allows the sintered precursor layer 2 to have a smoother surface.

[0081] The average particle size of the sinterable particles is determined by a particle size distribution measurement method described in detail below. Note that the above average particle size refers to the average particle size of all the sinterable particles contained in the sintering precursor layer 2 .

[0082] The sintered precursor layer 2 preferably contains 60% by mass or more of sinterable particles, more preferably 65% by mass or more, further preferably 70% by mass or more, and most preferably 75% by mass or more. The sintered precursor layer 2 preferably contains 99% by mass or less of sinterable particles, more preferably 98% by mass or less, and further preferably 97% by mass or less.

[0083] From another viewpoint, the sintering precursor layer 2 preferably contains 30% by volume or more and 70% by volume or less of sinterable particles.

[0084] By setting the content of the sinterable particles within the above range, when the sinterable particles are sintered by sintering to bond a semiconductor element such as a semiconductor chip X to a substrate, the bond achieved by the sintered precursor layer 2 can be sufficiently reliable.

[0085] The volume content of the sinterable particles in the sintering precursor layer 2 is preferably higher than the volume content of the sinterable particles in the adhesion layer 1. This allows the sintered sintering precursor layer 2 to have a denser layer.

[0086] The content (mass %) of sinterable particles in the sintered precursor layer 2 can be calculated based on the measured value of the ash content remaining after burning the sintered precursor layer 2. For example, the measurement can be performed using a thermogravimetric analyzer (e.g., TG209F1) according to the following procedure. It should be noted that the measurement using the thermogravimetric analyzer is preferably performed under a nitrogen flow.

[0087] (1) A measurement sample of the sintered precursor layer 2 weighing approximately 50 mg is heated from room temperature (23±2° C.) to 650° C.

[0088] (2) The organic binder in the measurement sample is thermally decomposed by maintaining the sample at a temperature of 650°C for 30 minutes.

[0089] (3) Calculate the mass ratio of the residual component (ash) to the weighed value of the measurement sample (approximately 50 mg).

[0090] On the other hand, the content (volume %) of the sinterable particles in the sintering precursor layer 2 is calculated by dividing the cumulative value of the area of the sinterable particles in the SEM observation image obtained by observing the cross section of the sintering precursor layer 2 using a scanning microscope by the total area of the observation image.

[0091] In this embodiment, the sintered precursor layer 2 preferably contains a pyrolyzable binder (particularly a pyrolyzable polymer binder) and a volatile binder as organic binders. The volatile binder is an organic binder component that completes weight loss (completely desorbs to 0% weight) at a lower temperature than the pyrolyzable polymer binder when measured by thermogravimetric analysis (TGA).

[0092] The pyrolyzable polymer binder is a binder that thermally decomposes during sintering. The pyrolyzable polymer binder also has the function of maintaining the sintered precursor layer 2 in a sheet shape until sintering. To fully utilize this function, the pyrolyzable polymer binder is preferably in a solid state at room temperature (23±2°C).

[0093] Examples of the thermally decomposable polymer binder include polycarbonate resin and acrylic resin. The sintered precursor layer 2 preferably includes at least one of polycarbonate resin and acrylic resin as the thermally decomposable polymer binder. The sintered precursor layer 2 may include only polycarbonate resin as the thermally decomposable polymer binder.

[0094] Examples of polycarbonate resins include aliphatic polycarbonates having only aliphatic chains and containing no aromatic structure such as a benzene ring between carbonates (-OC(=O)-O-) in the main chain, and aromatic polycarbonates having an aromatic structure between carbonates (-OC(=O)-O-) in the main chain.

[0095] Examples of the aliphatic polycarbonate include polyethylene carbonate and polypropylene carbonate.

[0096] Examples of the aromatic polycarbonate include polycarbonates containing a bisphenol A structure in the main chain.

[0097] Examples of the acrylic resin include polymers of (meth)acrylic acid alkyl esters having a linear or branched alkyl moiety with a carbon number of 4 to 18. The term "(meth)acrylic" encompasses both "acrylic" and "methacrylic."

[0098] Examples of the alkyl group (alkyl moiety) of the (meth)acrylate include methyl, ethyl, propyl, isopropyl, n-butyl, tert-butyl, isobutyl, pentyl, isopentyl, hexyl, heptyl, cyclohexyl, 2-ethylhexyl, octyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, lauryl, tridecyl, tetradecyl, stearyl, and octadecyl.

[0099] The acrylic resin may contain polymerized units derived from other monomers in addition to the above-mentioned (meth)acrylates in the molecule. Examples of other monomers include carboxyl group-containing monomers, acid anhydride monomers, hydroxyl group-containing monomers, sulfonic acid group-containing monomers, and phosphoric acid group-containing monomers.

[0100] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid.

[0101] Examples of the acid anhydride monomer include maleic anhydride and itaconic anhydride.

[0102] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate.

[0103] Examples of the sulfonic acid group-containing monomer include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl(meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.

[0104] Examples of the phosphoric acid group-containing monomer include 2-hydroxyethyl acryloyl phosphate.

[0105] In this embodiment, the volatile binder preferably exhibits a 1×10 5 The viscosity is a liquid with a viscosity of Pa·s or less. The viscosity is measured using a dynamic viscoelasticity measuring device (machine name "HAAKE MARS III", manufactured by Thermo Fisher Scientific). Specifically, as a jig, parallel plates with a diameter of 20 mm are used, the gap between the plates is set to 100 μm, and the shear rate in the rotational shear is set to 1 s. -1 , measure the viscosity.

[0106] Examples of the volatile binder include terpene alcohols, alcohols other than terpene alcohols, alkylene glycol alkyl ethers, and ethers other than alkylene glycol alkyl ethers.

[0107] Examples of the terpene alcohols include isobornylcyclohexanol, citronellol, geraniol, nerol, carveol, and α-terpineol.

[0108] Examples of alcohols other than terpene alcohols include pentanol, hexanol, heptanol, octanol, 1-decanol, ethylene glycol, diethylene glycol, propylene glycol, butanediol, and 2,4-diethyl-1,5-pentanediol.

[0109] Examples of the alkylene glycol alkyl ethers include ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl methyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, and tripropylene glycol dimethyl ether.

[0110] Examples of ethers other than alkylene glycol alkyl ethers include ethylene glycol ethyl ether acetate, ethylene glycol butyl ethyl acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ethyl acetate, and dipropylene glycol methyl ether acetate.

[0111] As the volatile binder, one type may be used alone or two or more types may be used in combination.

[0112] As the volatile binder, from the viewpoint of stability at room temperature, terpene alcohols are preferred, and among terpene alcohols, isobornylcyclohexanol is more preferred.

[0113] Isobornylcyclohexanol is also known as 4-[1,7,7-trimethylbicyclo[2.2.1]heptan-2-yl]cyclohexanol. The boiling point of isobornylcyclohexanol is between 308°C and 318°C. The vapor pressure of isobornylcyclohexanol at 25°C is 0.00003 mmHg.

[0114] Isobornylcyclohexanol has the following characteristic physical properties. Specifically, under a nitrogen flow rate of 200 mL / min and a temperature increase rate of 10°C / min, when heated from room temperature (23±2°C) to 600°C, isobornylcyclohexanol exhibits a significant mass decrease above 100°C and evaporates at 245°C (no mass decrease beyond this level is observed). Furthermore, it exhibits an extremely high viscosity of 1,000,000 mPa·s at 25°C, but a relatively low viscosity of 1,000 mPa·s or less at 60°C. The mass decrease is the value obtained when the mass decrease rate at the measurement start temperature (room temperature) is set to 0%.

[0115] As described above, isobornylcyclohexanol exhibits an extremely high viscosity at 25°C, making it easy for the sintered precursor layer 2 to maintain its sheet shape at room temperature. On the other hand, isobornylcyclohexanol exhibits a relatively low viscosity at 60°C, showing tackiness. In other words, the sintered precursor layer 2 containing isobornylcyclohexanol can maintain its sheet shape sufficiently at room temperature and can maintain tackiness at temperatures above 60°C.

[0116] Therefore, the sintered precursor layer 2 contains isobornylcyclohexanol as a volatile binder, thereby improving its temporary fixation to an adherend such as a substrate. In other words, it is possible to further suppress the semiconductor element from being displaced from its mounting position after being temporarily fixed to the adherend, or to prevent the sintered precursor layer 2 from floating from the adherend.

[0117] The temperature at which the semiconductor element is temporarily fixed to an adherend such as a substrate via the sintered precursor layer 2 is, for example, 30°C to 200°C. This temperature is preferably 50°C or higher, and more preferably 70°C or higher. At this temperature, isobornylcyclohexanol exhibits viscosity for the reasons described above. This temperature may be 150°C or lower, or 125°C or lower.

[0118] The sintered precursor layer 2 may contain 1 mass % or more of the organic binder, 2 mass % or more, or 3 mass % or more. The sintered precursor layer 2 preferably contains 3 mass % or more of the organic binder, and more preferably contains 5 mass % or more.

[0119] The sintered precursor layer 2 may contain 40% by mass or less of the organic binder, 35% by mass or less, or 30% by mass or less. The sintered precursor layer 2 preferably contains 20% by mass or less, and more preferably 10% by mass or less of the organic binder.

[0120] When the sintered precursor layer 2 contains the aforementioned pyrolyzable polymer binder and the aforementioned volatile binder as organic binders, the proportion (%) of the pyrolyzable polymer binder in the total amount of the pyrolyzable polymer binder and the volatile binder is preferably 5% by mass or greater, more preferably 10% by mass or greater, and even more preferably 20% by mass or greater. The aforementioned proportion (%) is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. In the sintered precursor layer 2, the content of the volatile binder may be greater than the content of the pyrolyzable polymer binder.

[0121] The sintering precursor layer 2 preferably contains 0.01 mass % or more of the thermally decomposable polymer binder, more preferably 0.05 mass % or more, further preferably 0.10 mass % or more, and even more preferably 0.20 mass % or more.

[0122] The sintering precursor layer 2 preferably contains 20.0 mass % or less of the thermally decomposable polymer binder, more preferably 10.0 mass % or less, further preferably 7.5 mass % or less, and even more preferably 5.0 mass % or less.

[0123] The sintering precursor layer 2 preferably contains 0.5 mass % or more of the volatile binder, more preferably 1.0 mass % or more, further preferably 1.5 mass % or more, and even more preferably 2.0 mass % or more.

[0124] The sintering precursor layer 2 preferably contains 20.0% by mass or less of a volatile binder, more preferably 15.0% by mass or less, and even more preferably 10.0% by mass or less.

[0125] The sintering precursor layer 2 may have a single-layer structure. Alternatively, the sintering precursor layer 2 may have a multilayer structure in which a plurality of layers are stacked.

[0126] In this embodiment, the thickness of the sintering precursor layer 2 is preferably 5 μm or greater. Alternatively, the thickness of the sintering precursor layer 2 may be 300 μm or less, 200 μm or less, or 100 μm or less. The sintering precursor layer 2 may be thicker than the adhesion layer 1 .

[0127] The thickness of the sintered precursor layer 2 is calculated by, for example, measuring the thickness at five randomly selected locations using a digital micrometer (manufactured by PEACOCK, Model: R-205) and averaging these measured values.

[0128] Next, the adhesion layer 1 of the thermal bonding sheet 10 according to the present embodiment will be described in detail.

[0129] [Adhesive layer of the heat bonding sheet]

[0130] In this embodiment, the adhesion layer 1 contains sinterable particles and an organic binder, similarly to the sintering precursor layer 2. The details of the sinterable particles and the organic binder are as described above. Below, in the description related to the adhesion layer, only the differences from the description of the sintering precursor layer 2 are listed. Therefore, the same description as for the sintering precursor layer 2 is not repeated.

[0131] The particle size distribution of the sintered particles contained in the adhesion layer 1 has at least two peak vertices when the particle size distribution is measured. Specifically, in the particle size distribution diagram obtained by measuring the particle size distribution using the following measurement conditions, at least two peaks appear on the large particle size side and the small particle size side. The peak vertices of each peak are separated from each other. In the particle size distribution diagram, for example, the horizontal axis takes the particle size in the range of 1 μm to 10,000 μm, and the vertical axis takes the frequency (%). When the height of the peak vertices (frequency (%)) is less than 0.1%, it is not considered as a peak on the small particle size side.

[0132] For example, in the adhesion layer 1, by mixing a powder having a larger average particle size (large particle group) with a powder having a smaller average particle size (small particle group), at least two peaks appear in the particle size distribution diagram as described above. In other words, the adhesion layer 1 contains a powder having a larger average particle size (large particle group) and a powder having a smaller average particle size (small particle group). Since the adhesion layer 1 contains the large particle group, by mixing at least the sinterable particles with the organic binder when making the adhesion layer 1, the organic binder is finely pulverized by the large particle group having a larger particle size, and as a result, the uniformity of the interior of the adhesion layer 1 becomes higher.

[0133] The material of the particles constituting the large particle group and the material of the particles constituting the small particle group may be the same as or different from each other. At least a portion of the particles constituting the large particle group and at least a portion of the particles constituting the small particle group preferably contain the same metal element. "Containing the same metal element" means: respectively containing the same metal or a compound containing the same metal element (the same metal oxide or a metal oxide of the same metal element with different oxidation numbers, etc.). Thus, by sintering treatment, the particles are easily sintered to each other inside the bonding layer 1. Therefore, the sintered precursor layer 2 can form a denser layer after sintering treatment.

[0134] Details of the particle size distribution measurement method are shown below.

[0135] [Measurement conditions for particle size distribution measurement]

[0136] Measuring equipment: Laser diffraction-scattering particle size distribution analyzer

[0137] (For example, Microtrac MT3000II, MicrotracBEL)

[0138] (Pretreatment of measurement samples)

[0139] Using a cryostat, at least one thin section of the sample was collected from the surface of the adhesive layer 1, which had been frozen in liquid nitrogen. 0.1 g of the sample was then placed in a beaker, 1 g of an alcoholic dispersion solvent (commonly known as "Solmix") was added, and the sample was dispersed for 10 seconds using an ultrasonic disperser. The particle size distribution was then measured using a laser diffraction scattering particle size analyzer under the following conditions.

[0140] (Laser diffraction scattering particle size analyzer settings)

[0141] Number of measurements: 2 times

[0142] Measurement time: 30 seconds

[0143] Set shape: spherical

[0144] Measurement mode: Ag (reflect)

[0145] Specific gravity of particles: 10.5

[0146] Solvent for measurement: ethanol

[0147] Refractive index of solvent: 1.36

[0148] Measurement temperature: 25°C

[0149] Particle size distribution: volume basis

[0150] Average particle size: median particle size (D50)

[0151] The content of the sinterable particles in the adhesion layer 1 is, for example, more than 30 mass %, preferably more than 60 mass %. The content of the sinterable particles in the adhesion layer 1 is, for example, below 95 mass %, preferably below 90 mass %. By being the above-mentioned numerical range, the adhesion of the adhesion layer 1 to adherends such as wafers becomes better. In addition, by sintering treatment, the sinterable particles are sintered to each other, and when semiconductor elements such as semiconductor chip X are bonded to substrate, the bonding achieved by the adhesion layer 1 after the sintering treatment can give play to sufficient reliability.

[0152] The content of the sinterable particles in the adhesion layer 1 is, for example, 5% by volume or more, preferably 15% by volume or more. The content of the sinterable particles in the adhesion layer 1 is, for example, 40% by volume or less, preferably 35% by volume or less. By being within this numerical range, the adhesion between the adhesion layer 1 and adherends such as wafers becomes better. The content of the sinterable particles in the adhesion layer 1 can be obtained in the same manner as the volume % of the sinterable particles in the above-mentioned sintering precursor layer 2.

[0153] The proportion of the large particle group in the sinterable particles contained in the adhesive layer 1 is preferably 5% or more and 30% or less, based on volume %. This numerical range improves the adhesion between the adhesive layer 1 and an adherend such as a wafer. This proportion is the proportion of the sinterable particles in the large particle group to the total sintered particles, as determined by the particle size distribution measurement (laser diffraction-scattering measurement) described above, and is calculated based on volume %.

[0154] Specifically, the peak located on the large particle side of the highest and second-highest peaks in the particle size distribution is considered the peak of the large particle group of sintered particles. Based on the multiple peaks appearing in the particle size distribution, the cumulative counts of all sintered particles and the cumulative counts of the peaks of the large particle group are calculated. Therefore, by setting the cumulative counts of all sintered particles in volume conversion to 100%, the proportion of the large particle group in the total sintered particles is calculated as a numerical value [%].

[0155] It should be noted that, in either side of the peak, when the peak curve extends upward from the 0 point height in the longitudinal axis of the particle size distribution diagram, in principle, the point at the 0 point height of the peak curve is considered as the boundary of the peak (that is, peak starting point or ending point). In addition, when the lowest point of the valley between 2 adjacent peaks is located at a position higher than the 0 point in the longitudinal axis of the particle size distribution diagram (when a part of two peaks overlaps), in principle, the line drawn out by the lowest point and parallel to the longitudinal axis is considered as the boundary of 2 peaks. In addition, the horizontal axis (the horizontal axis passing through the 0 point in the longitudinal axis) is considered as the baseline of the peak. By calculating the count in the part surrounded by the boundary, the above-mentioned baseline and the peak curve set as above, it is possible to obtain the ratio etc. shared by the large particle group among the above-mentioned sinterable particles.

[0156] The ratio (P2 / P1) of the average particle size P2 of the large particle group contained in the adhesion layer 1 to the average particle size P1 of the small particle group can be 10 or more and 1000 or less, or 100 or less, or 50 or less. As the ratio increases, the organic binder is broken down into smaller pieces as described above, resulting in a higher uniformity within the adhesion layer 1. When three or more peaks appear in the particle size distribution, one of the highest and second highest peaks in the particle size distribution, located on the large particle side, can be regarded as the peak of the large particle group of sinterable particles, and the other peak can be regarded as the peak of the small particle group of sinterable particles.

[0157] It should be noted that the average particle size P1 of the small particle group and the average particle size P2 of the large particle group refer to the particle size values at the peak apex of each peak in the particle size distribution diagram. Therefore, in other words, the ratio (P2 / P1) of the particle size value P2 at the peak apex of the large particle group to the particle size value P1 at the peak apex of the small particle group in the particle size distribution diagram is preferably within the above-mentioned range.

[0158] The average particle size P1 of the small particle group (the particle size value P1 at the peak apex of the small particle group) can be, for example, 0.005 μm or more and 1 μm or less. The average particle size P2 of the large particle group (the particle size value P2 at the peak apex of the large particle group) can be, for example, 0.5 μm or more and 10 μm or less. Peaks with apexes falling within these ranges can be considered peaks of the large particle group and the small particle group, respectively.

[0159] The adhesive layer 1 may contain 1% by mass or more of the organic binder, or 2% by mass or more. The adhesive layer 1 may contain 40% by mass or less of the organic binder, or 35% by mass or less.

[0160] When the adhesive layer 1 contains the aforementioned pyrolyzable polymer binder and the aforementioned volatile binder as organic binders, the proportion (%) of the pyrolyzable polymer binder in the total amount of the pyrolyzable polymer binder and the volatile binder is preferably 5% by mass or greater, more preferably 10% by mass or greater. This proportion (%) is preferably 60% by mass or less, more preferably 50% by mass or less. It should be noted that the content of the volatile binder in the adhesive layer 1 may be greater than the content of the pyrolyzable polymer binder.

[0161] The adhesive layer 1 may contain 0.01% by mass or more of the thermally decomposable polymer binder, or 0.05% by mass or more, or 20.0% by mass or less, or 10.0% by mass or less.

[0162] The adhesive layer 1 may contain 0.5% by mass or more of the volatile binder, or 1.5% by mass or more. The adhesive layer 1 may contain 40.0% by mass or less of the volatile binder, or 30.0% by mass or less.

[0163] The thickness of the adhesive layer 1 can be, for example, 1 μm or more and 100 μm or less. The thickness of the adhesive layer 1 is preferably 2 μm or more. Furthermore, the thickness of the adhesive layer 1 is preferably 50 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. The thickness of the adhesive layer 1 is measured in the same manner as the thickness of the sintered precursor layer 2 described above.

[0164] Next, the component migration preventing layer 3 of the thermal bonding sheet 10 of the present embodiment will be described in detail. The thermal bonding sheet 10 may or may not include the component migration preventing layer 3.

[0165] [Component Migration Prevention Layer of Thermal Bonding Sheet]

[0166] In this embodiment, the component migration preventing layer 3 of the thermal bonding sheet 10 functions as a support in the thermal bonding sheet 10. The component migration preventing layer 3 contains at least a resin and is made of, for example, a plastic film.

[0167] Examples of the material of the plastic film include polyolefin resins, polyester resins, polyurethane resins, polycarbonate resins, polyetheretherketone resins, polyimide resins, polyetherimide resins, polyamide resins, wholly aromatic polyamide resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyphenylene sulfide resins, aromatic polyamide resins, fluororesins, cellulose resins, and silicone resins.

[0168] It should be noted that the component migration prevention layer 3 may be formed of one material or may be formed of two or more materials.

[0169] Examples of the polyolefin resin include low-density polyethylene resin, linear low-density polyethylene resin, medium-density polyethylene resin, high-density polyethylene resin, ultra-low-density polyethylene resin, random copolymer polypropylene resin, block copolymer polypropylene resin, homopolymer polypropylene resin, polybutene resin, polymethylpentene resin, ethylene-vinyl acetate copolymer resin, ionomer resin, ethylene-butene copolymer resin, and ethylene-hexene copolymer resin.

[0170] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, and polybutylene terephthalate resin.

[0171] The component migration preventing layer 3 may have a single-layer structure or a multi-layer structure. It should be noted that a single-layer structure refers to a structure formed from a single material. For example, a component migration preventing layer 3 formed by laminating two or more layers formed from a single material has a single-layer structure. On the other hand, a component migration preventing layer 3 formed by laminating two or more layers formed from different materials has a multi-layer structure.

[0172] When the component migration preventing layer 3 is a plastic film, the component migration preventing layer 3 may be a non-stretched film or a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film.

[0173] Alternatively, the component migration prevention layer 3 may be a release liner having a release treatment applied to the surface in contact with the sintered precursor layer 2. For example, a release agent may be applied to one surface of the component migration prevention layer 3 in contact with the sintered precursor layer 2. In this case, when manufacturing a semiconductor device, the small pieces of the sintered precursor layer 2 (small pieces 2' of the sintered precursor layer) can be easily peeled off from one surface of the component migration prevention layer 3 (release liner).

[0174] The thickness of the component migration prevention layer 3 is preferably 2 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. The thickness of the component migration prevention layer 3 is preferably 5000 μm or less, more preferably 4000 μm or less, and further preferably 3000 μm or less.

[0175] The thickness of the component migration prevention layer 3 is measured in the same manner as the thickness of the sintering precursor layer 2 described above.

[0176] In the thermal bonding sheet 100 with a dicing tape of this embodiment, for example, Figure 1B As shown, the thermal bonding sheet 10 and the dicing tape 20 are provided, which are superimposed on one surface of the thermal bonding sheet 10. In the thermal bonding sheet 100 with a dicing tape, the sintering precursor layer 2 is disposed between the adhesion layer 1 and the dicing tape 20.

[0177] The dicing tape 20 includes a base layer 21 and an adhesive layer 22 superimposed on one side of the base layer 21. The base layer 21 of the dicing tape 20 is formed, for example, from a resin film, and the adhesive layer 22 is formed, for example, from an adhesive resin composition containing an acrylic resin. Such dicing tapes 20 are commercially available.

[0178] It should be noted that when the thermal bonding sheet 10 includes the component migration prevention layer 3, for example, the component migration prevention layer 3 overlaps with the adhesive layer 22 of the dicing tape 20. On the other hand, when the thermal bonding sheet 10 does not include the component migration prevention layer 3, for example, the sintered precursor layer 2 of the thermal bonding sheet 10 overlaps with the adhesive layer 22 of the dicing tape 20.

[0179] Next, a method for producing the thermal bonding sheet will be described.

[0180] The method for producing the thermal bonding sheet comprises, for example, the steps of forming a sintering precursor layer, forming an adhesive layer, and laminating the sintering precursor layer and the adhesive layer. Optionally, the method further comprises laminating a component migration prevention layer on one side of the sintering precursor layer.

[0181] The step of forming the sintering precursor layer includes, for example, the steps of preparing a varnish containing sinterable particles containing a conductive metal, an organic binder, and an organic solvent; and volatilizing the organic solvent from the varnish to form the sintering precursor layer.

[0182] The step of forming the adhesion layer includes, for example, the steps of preparing a varnish containing sinterable particles containing a conductive metal, an organic binder, and an organic solvent; and volatilizing the organic solvent from the varnish to form the adhesion layer.

[0183] The steps of forming the sintering precursor layer and the step of forming the adhesion layer are basically the same. Specific examples of each step are shown below.

[0184] In the step of preparing the varnish, for example, the sinterable particles, the organic binder, and an organic solvent are mixed to disperse the sinterable particles in the organic solvent and dissolve the organic binder in the organic solvent, thereby preparing the varnish.

[0185] As the organic solvent, for example, alcohols such as ethanol, ketones such as methyl ethyl ketone (MEK), etc. can be used.

[0186] The mixing temperature during the preparation of the varnish is not particularly limited, and is, for example, 5° C. to 70° C. The mixing method is not particularly limited, and a common mixing method using a stirring device can be employed.

[0187] The solid content concentration in the varnish is, for example, 30% to 80% by mass. The solid content concentration in the varnish may be 40% to 50% by mass. The solid content concentration in the varnish may be 70% to 70% by mass. It should be noted that the solid content refers to components other than the organic solvent, such as the total amount of the sinterable particles and the organic binder.

[0188] The viscosity of the varnish at 23°C is, for example, 1.0 [Pa·s] or more and 7.0 [Pa·s] or less. This viscosity is measured using an E-type viscometer (e.g., "RE-85," manufactured by Toki Sangyo Co., Ltd.). Specifically, a "1°34" x R24" conical rotor is used as a jig, with a sample volume of 1.1 mL and a rotation speed of 1.0 rpm.

[0189] In the step of forming the sintering precursor layer, for example, a varnish is applied to a release liner in a predetermined thickness to form a coating film, and then the coating film is heated to volatilize the organic solvent.

[0190] In the step of forming the adhesion layer, for example, a varnish is applied to a release liner at a predetermined thickness to form a coating film, which is then heated to volatilize the organic solvent.

[0191] In the step of laminating the sintering precursor layer and the adhesive layer, the sintering precursor layer on the release liner and the adhesive layer on the release liner are superimposed on each other.

[0192] If necessary, the release liner attached to the sintering precursor layer is removed, and the component migration prevention layer is superimposed on the exposed sintering precursor layer. Alternatively, the release liner attached to the sintering precursor layer may be left as is as the component migration prevention layer.

[0193] The thermal bonding sheet 10 manufactured as described above can be used as an auxiliary member in manufacturing a semiconductor device, for example.

[0194] [Method of Using a Thermal Bonding Sheet (Method of Manufacturing a Semiconductor Device)]

[0195] Next, an example of a method for manufacturing a semiconductor device using the thermal bonding sheet 10 according to this embodiment will be described with reference to the drawings.

[0196] It should be noted that, in the method for manufacturing a semiconductor device, the adherend to be bonded to the bonding layer 1 or the sintered precursor layer 2 of the heat bonding sheet 10 is not limited to the following examples. As the adherend, for example, a semiconductor wafer, a substrate, a heat sink or a fixture (used in the so-called copper clip bonding (clip bonding)) can be listed. In addition, as the adherend, a metal pad or a metal plate can also be listed. For example, a stack of a bonding layer 1 and a sintered precursor layer 2 (a first stack) is bonded to one side of a semiconductor chip, and after the semiconductor chip and the adherend are bonded via the first stack, a stack of a bonding layer 1 and a sintered precursor layer 2 (a second stack) is further bonded to the other side of the semiconductor chip. Furthermore, the semiconductor chip and the metal pad or metal plate can be bonded via the second stack. In this case, for example, the bonding layer 1 of the first stack can be bonded to the semiconductor wafer (semiconductor chip), and the bonding layer 1 of the second stack can be bonded to the metal pad or metal plate.

[0197] The method for manufacturing a semiconductor device according to this embodiment is implemented using, for example, the following components: a semiconductor wafer W for obtaining a plurality of semiconductor chips X, a substrate having a plurality of mounting areas for mounting the plurality of semiconductor chips X, the thermal bonding sheet 10, and a dicing tape 20 (see FIG. Figure 1B), and a pressing member for temporarily fixing the plurality of semiconductor chips X to the plurality of mounting areas.

[0198] The following describes an example of a semiconductor chip X mounted on a substrate such as a DBC (Direct Bonded Copper) substrate or an AMB (Active Metal Brazing) substrate using a collet A as a pressing member. These substrates have, for example, a ceramic insulating layer D, and copper die pads E and a copper thin layer F disposed on both sides of the ceramic insulating layer D. The copper die pad E is an area for mounting the semiconductor chip X (hereinafter also referred to as the mounting area) (see Figure 3A ).

[0199] First, the semiconductor wafer W is diced on the dicing tape 20 to obtain a plurality of semiconductor chips X from the semiconductor wafer W (see FIG. Figure 2A and Figure 2B ). Specifically, a semiconductor wafer W is attached to the exposed surface of the heat bonding sheet 10, and a dicing ring R is attached to the adhesive layer 22 of the dicing tape 20. Then, the semiconductor wafer W is divided into a plurality of small pieces, thereby obtaining a semiconductor chip X. More specifically, the heat bonding sheet 10 and the semiconductor wafer W are cut into small pieces (so-called full cut) using a dicing saw S or the like, and the small pieces of heat bonding sheet 10' and semiconductor chip X are produced on the dicing tape 20. As the dicing tape 20, a commercially available product can be used.

[0200] It should be noted that when the thermal bonding sheet 10 includes a component migration prevention layer 3 and the component migration prevention layer 3 is a release liner, the adhesive layer 1 and the sintering precursor layer 2 in the thermal bonding sheet 10 excluding the component migration prevention layer 3 can be cut (so-called half-cutting). In this case, the small pieces of the sintering precursor layer 2 (small pieces 2' of the sintering precursor layer) are peeled off from one surface of the component migration prevention layer 3 (release liner), and as described in detail later, the semiconductor chip X and the small piece 10' of the thermal bonding sheet can be picked up.

[0201] The obtained semiconductor chip X is, for example, in the shape of a rectangular thin plate. The thickness of the semiconductor chip X is, for example, 10 μm or more and 500 μm or less. The thickness of the semiconductor chip X is preferably 20 μm or more and 400 μm or less.

[0202] The area of the semiconductor chip X when viewed from one side in the thickness direction is, for example, 0.01 mm 2 Above and 1000mm 2 The area is preferably 0.04 mm 2 Above and 500mm 2 the following.

[0203] Then, if Figure 2C As shown, the semiconductor chip X, with the thermal bonding sheet small piece 10' attached thereto, is peeled from the adhesive layer 22 of the dicing tape 20. Specifically, while the dicing tape 20 with the dicing ring R attached thereto is secured by a holding tool Q, the pin member P is raised to lift the semiconductor chip X and the thermal bonding sheet small piece 10', which are to be picked up, through the dicing tape 20. The lifted semiconductor chip X and thermal bonding sheet small piece 10' are held by the collet A.

[0204] It should be noted that the following steps may be performed instead of Figure 2A and Figure 2B In detail, as shown in Figure 2D As shown, a plurality of fragile regions T for cutting are formed inside the semiconductor wafer W by performing stealth dicing on the semiconductor wafer W on the dicing tape 20 .

[0205] During stealth dicing, laser light directed at a focused point is irradiated into the interior of the semiconductor wafer W. This forms a fragile region T within the semiconductor wafer W through ablation based on multiphoton absorption. It should be noted that before or after stealth dicing, the back side of the semiconductor wafer W may be ground to reduce its thickness.

[0206] After the stealth cutting process, the semiconductor wafer W is as follows Figure 2E As shown, the dicing tape 20 is expanded and cut along the brittle region T. Specifically, the dicing tape 20, carrying the semiconductor wafer W that has undergone the stealth dicing process, is first fixed to the holding tool Q of the expansion device. Next, the dicing tape 20 is stretched (expanded) to expand its area, thereby cutting the semiconductor wafer W. Specifically, a plurality of lifting members U are raised from the bottom side of the dicing tape 20 to stretch (expand) the dicing tape 20 in the surface direction. The temperature conditions during expansion are, for example, above -20°C and below 70°C. This expansion forms cracks in the brittle region T of the semiconductor wafer W, and the semiconductor wafer W is fragmented into semiconductor chips X. Thereafter, the lifting members U are lowered to release the expanded state of the dicing tape 20. After expansion, the dicing tape 20 can be heated at a portion closer to the periphery than the group of semiconductor chips X to shrink it. The heating temperature is, for example, above 100°C and below 300°C.

[0207] By performing such a process, the semiconductor chip X can be formed on the dicing tape 20. Figure 2C As shown, the semiconductor chip X in a state where the small piece 10 ′ of the thermal bonding sheet is bonded thereto is peeled from the adhesive layer 22 of the dicing tape 20 .

[0208] Next, a substrate (for example, a laminate of a ceramic insulating layer D, a copper die pad E, and a copper thin layer F) is placed on a base H (see Figure 3A ).

[0209] Then, the collet A, which holds the semiconductor chip X and is set to a temperature within the range of 25°C to 150°C, is lowered vertically, causing the small piece 10' of the heat bonding sheet attached to the semiconductor chip X to abut against the copper die pad E. The collet A then presses (pushes) the semiconductor chip X toward the copper die pad E. After performing the above operations and temporarily securing one semiconductor chip X to the copper die pad E, the same operations are repeated.

[0210] Thus, the plurality of semiconductor chips X are temporarily fixed to the copper die pad E via the small piece 10' of the heat bonding sheet (see FIG. Figure 3A and Figure 3B ).

[0211] The pressure when the semiconductor chip X is pressed against the copper die pad E is preferably 0.01 MPa to 50 MPa, and more preferably 0.1 MPa to 30 MPa.

[0212] It should be noted that the substrate to which the small piece 10' serving as the heat-bonding sheet is adhered may be a lead frame. A general lead frame can be used as the lead frame. For example, a lead frame made of Cu plated with Ag, or a lead frame made of Cu plated with Ni, Pd, and Au in this order (Palladium Pre-Plated Lead Frame, Pd-PPF) can be used.

[0213] It should be noted that the collet A can be heated to a temperature at which the sinterable particles contained in the small pieces 10' of the heat bonding sheet can be sintered when temporarily fixing each semiconductor chip X. This allows a primary sintering process of the sinterable particles contained in the small pieces 10' of the heat bonding sheet to be performed.

[0214] If the sinterable particles contained in the small piece 10' of the heat-bonding sheet can be sintered at a heating temperature of 400°C or less, it is preferable to heat the collet A to a temperature of 200°C or higher. Heating the collet A to 200°C or higher allows the sinterable particles to be more fully sintered. Therefore, the small piece 10' of the heat-bonding sheet allows the semiconductor chip X to be more securely bonded to the copper die pad E. In other words, the bonding reliability of the semiconductor chip X to the substrate is further improved.

[0215] When performing the primary sintering process, it is preferable to heat the collet A quickly (about 5 seconds). The collet A is preferably heated at a rate of 30°C / sec or higher, more preferably 45°C / sec or higher.

[0216] It should be noted that the primary sintering process can also be performed by heating not only the collet A but also the base H at the same temperature as described above. This allows the heating of the small pieces 10' of the heat-bonding sheet from both sides in the thickness direction, thereby enabling the sinterable particles to be more fully sintered. Consequently, the heat-bonding small pieces 10' enable the semiconductor chip X to be more fully bonded to the copper die pad E. In other words, the bonding reliability of the semiconductor chip X to the substrate is further improved.

[0217] The temperature of the heated base H is preferably lower than or equal to a temperature that suppresses oxidation of the copper die pad E or the copper thin layer F. The heating temperature of the base H is preferably 150° C. or lower.

[0218] When the primary sintering process is performed as described above, for example, by lifting the collet A after the primary sintering process to separate the semiconductor chip X from the collet A, the temperature of the collet A can be lowered to a temperature (eg, 50° C.) at which the sinterable particles are not easily sintered.

[0219] In addition, when performing a single sintering process on all the small pieces 10 ′ of the thermal bonding sheet, bonding wires can be bonded to necessary locations after all the semiconductor chips X are bonded.

[0220] In the method for manufacturing a semiconductor device according to this embodiment, after temporarily attaching the plurality of semiconductor chips X to the substrate, a heating step may be performed to heat the small pieces 10' of the heat-bonding sheet to a temperature at which the sinterable particles can be sintered. In the heating step, a compressive force may be applied to at least one of the plurality of small pieces 10' of the heat-bonding sheet in the thickness direction while heating the small pieces.

[0221] When the primary sintering process is performed, the heating step corresponds to the secondary sintering process. In other words, the sintering process can be performed by both the primary sintering process and the secondary sintering process (the heating step).

[0222] More specifically, in the method for manufacturing a semiconductor device according to this embodiment, the sintering process can be performed as follows.

[0223] During the heating step of the sintering process, for example, at least one of the plurality of small pieces 10' of the heat bonding sheet is pressed and heated in the thickness direction. Specifically, after temporarily fixing the semiconductor chip X, a heat-pressing device configured to heat the small piece 10' of the heat bonding sheet is used to apply a compressive force in the thickness direction and heat the small piece 10'.

[0224] Heating and pressing devices such as Figure 3C As shown, it is composed of two flat plates Z, Z. The two flat plates Z, Z are arranged so as to sandwich the base H, substrate (ceramic insulating layer D, copper die pad E, and copper thin layer F), and multiple semiconductor chips X. Furthermore, by applying a force that shortens the separation distance between the heated two flat plates, the small piece 10' of the heat bonding sheet is pressed and heated.

[0225] By performing the heating step in this manner, the plurality of small pieces 10' of the heat-bonding sheet can be pressed and heated simultaneously. Therefore, the semiconductor chip X can be firmly bonded to the substrate (copper die pad E) via the small pieces 10' of the heat-bonding sheet. This improves the bonding reliability of the semiconductor chip X to the substrate.

[0226] After the heating process is performed in this manner, the bonding wire can be bonded to a necessary location.

[0227] Alternatively, in the heating step, after all the semiconductor chips X to be bonded are temporarily fixed, the small piece 10' of the heat-bonding sheet may be heated without applying a compressive force in the thickness direction. In this case, heating is performed at a temperature at which the sinterable particles contained in the small piece 10' of the heat-bonding sheet can be sintered (e.g., any temperature within the range of 200°C to 400°C). Heating can be performed, for example, by heating the base H, or using an oven or reflow furnace.

[0228] By performing such a heating step, the semiconductor chip X can be firmly bonded to the substrate (copper die pad E) via the small piece 10' of the heating bonding sheet. Therefore, the bonding reliability of the semiconductor chip X to the substrate can be improved.

[0229] In the method for manufacturing the semiconductor device described in this embodiment, further steps may be performed.

[0230] For example, a wire bonding step of electrically connecting a portion of the semiconductor chip X and a portion of the substrate may be performed.

[0231] In addition, a sealing step may be performed to seal the semiconductor chip X and the thermal bonding sheet 10 ′ with a thermosetting resin such as epoxy resin. In the sealing step, a heat treatment is performed at a temperature of 150° C. to 200° C. to cure the thermosetting resin.

[0232] The sheet for thermal bonding according to the present embodiment is as exemplified above, but the present invention is not limited to the sheet for thermal bonding exemplified above.

[0233] That is, various forms used in general thermal bonding sheets and the like can be adopted within a range that does not impair the effects of the present invention.

[0234] Matters disclosed in this specification include the following matters.

[0235] (1) A sheet for thermal bonding comprising: a sintering precursor layer containing sinterable particles; and an adhesion layer superimposed on one surface of the sintering precursor layer.

[0236] The adhesion layer contains an organic binder and sinterable particles, and the content of the sinterable particles in the adhesion layer is 5% by volume or more and 40% by volume or less.

[0237] The sinterable particles contained in the adhesion layer have at least two peaks in their particle size distribution when the particle size distribution is measured.

[0238] In the thermal bonding sheet having this structure, the dispersibility of the organic binder in the adhesion layer is good.

[0239] (2) The thermal bonding sheet according to (1) above, wherein the volume content of the sinterable particles in the sintering precursor layer is higher than the volume content of the sinterable particles in the adhesion layer.

[0240] (3) The thermal bonding sheet according to (1) or (2), wherein the sintering precursor layer contains 30% by volume or more and 70% by volume or less of the sinterable particles.

[0241] (4) The thermal bonding sheet according to any one of (1) to (3), wherein the adhesion layer contains 15% by volume or more and 35% by volume or less of the sinterable particles.

[0242] (5) The sheet for thermal bonding according to any one of (1) to (4) above, wherein, when the peak located on the large particle side of the highest peak and the second highest peak in the particle size distribution is defined as the peak of the large particle group of the sinterable particles,

[0243] Among the sinterable particles contained in the adhesion layer, the proportion of the sinterable particles of the large particle group is 5% or more and 30% or less based on volume %.

[0244] (6) The thermal bonding sheet according to any one of (1) to (5), wherein both the sintering precursor layer and the adhesion layer contain a thermally decomposable binder as the organic binder.

[0245] (7) The thermal bonding sheet according to any one of (1) to (6), wherein the thickness of the sintering precursor layer is 5 μm to 100 μm, and the thickness of the adhesion layer is 2 μm to 20 μm.

[0246] (8) A thermal bonding sheet with a dicing tape, comprising the thermal bonding sheet according to any one of (1) to (7) above and a dicing tape superimposed on one surface of the thermal bonding sheet.

[0247] The sintering precursor layer of the thermal bonding sheet is arranged between the adhesion layer and the dicing tape.

[0248] (9) The sheet for thermal bonding according to (8) above, further comprising a component migration prevention layer.

[0249] The component migration prevention layer is disposed between the sintering precursor layer and the dicing tape.

[0250] Example

[0251] Next, the present invention will be described in more detail by way of experimental examples. However, the following examples are intended to illustrate the present invention in more detail and are not intended to limit the scope of the present invention.

[0252] (Raw materials for sintering precursor layer)

[0253] [Sintered particles]

[0254] First silver particles (small particle group):

[0255] Average particle size 60nm, manufactured by DOWA ELECTRONICS

[0256] Second silver particles (large particle group):

[0257] The average particle size is 1100nm, manufactured by Mitsui Mining and Smelting Co., Ltd.

[0258] [Organic binder]

[0259] Thermally decomposable polymer binder: polycarbonate resin:

[0260] Product name: "QPAC40", manufactured by Empower Materials

[0261] Volatile binder: isobornyl cyclohexanol

[0262] Product name: TERUSOLVE MTPH, manufactured by Nippon Terpene Chemicals Co., Ltd.

[0263] Organic solvent: methyl ethyl ketone (MEK)

[0264] [Release liner]

[0265] 1 pair of release film (product name "MRA38", made by Mitsui Plastics Co., Ltd.)

[0266] (Example 1)

[0267] [Preparation of sintered precursor layer]

[0268] The first silver particles (90 parts by mass), the second silver particles (10 parts by mass), a pyrolyzable polymer binder (4 parts by mass), and a volatile binder (12 parts by mass) were dissolved or suspended in methyl ethyl ketone (MEK) to prepare a varnish. Specifically, a mixing stirrer (model: "HM-500", manufactured by KEYENCE Corporation) was used and stirred for 3 minutes in a stirring mode.

[0269] Next, a varnish was applied to one side of the release liner, and then heated at 110° C. for 3 minutes to form a sintered precursor layer having a thickness of 25 μm.

[0270] [Production of Adhesive Layer]

[0271] The first silver particles (80 parts by mass) and the second silver particles (20 parts by mass) were measured to the amounts shown in Table 1. These silver particles, a pyrolyzable polymer binder (13 parts by mass), and a volatile binder (37 parts by mass) were dissolved or suspended in methyl ethyl ketone (MEK), and a varnish was prepared by the same method as described above.

[0272] Next, a varnish was applied to one side of the other release liner, and then heated at 110° C. for 3 minutes to form an adhesion layer having a thickness of 10 μm.

[0273] The content of all sinterable particles in the adhesion layer was measured by the above method. As a result, in Example 1, the total content of the first silver particles and the second silver particles in the adhesion layer was 30% by volume.

[0274] [Production of Sheet for Thermal Bonding]

[0275] The sintering precursor layer on the release liner and the adhesive layer on the release liner respectively produced as described above are bonded together to produce a sheet for thermal bonding.

[0276] (Examples 2 to 7, Comparative Example 1)

[0277] Sheets for thermal bonding were produced in the same manner as in Example 1 except that the compositions were changed to those shown in Table 1 and Table 2. The composition of the adhesive layer in each of the Examples and Comparative Examples is shown in Table 1 and Table 2, respectively.

[0278] [Table 1]

[0279]

[0280] *1: Total content of the first and second silver particles in the adhesion layer

[0281] *2: Ratio of the second silver particles to the total amount of the first and second silver particles

[0282] [Table 2]

[0283]

[0284] *1: Total content of the first and second silver particles in the adhesion layer

[0285] *2: Ratio of the second silver particles to the total amount of the first and second silver particles

[0286] [Measurement of Particle Size Distribution of Sinterable Particles Contained in Adhesive Layer]

[0287] The particle size distribution of the sinterable particles contained in the adhesive layer of each thermal bonding sheet manufactured as described above was measured using the aforementioned measurement method and conditions. The measurement results are shown in Tables 1 and 2. For example, in Example 1, the proportion of the second silver particles (large particle group) in the total sinterable particles in the adhesive layer was 20% based on volume content.

[0288] Two peaks were confirmed in the particle size distribution diagram of each example. Specific examples of the particle size distribution diagram after measurement (Example 5, Comparative Example 1) are shown in FIG. Figure 4 .

[0289] On the other hand, in the adhesion layer of Comparative Example 1, only one peak was confirmed in the particle size distribution chart.

[0290] <Ultrasonic Testing (SAT) Test (Evaluation of the Uniformity of the Adhesive Layer)>

[0291] A Cu substrate (20 mm × 20 mm × 3 mm thick) plated with Ag (5 μm thick) and a Si chip (5 mm × 5 mm × 0.2 mm thick) plated with Ti (0.1 μm thick) and Ag (0.75 μm thick) were prepared. Each thermal bonding sheet (containing only the sintering precursor layer and the adhesion layer) was sandwiched between the prepared Cu substrate and Si chip to produce a test laminate. The test laminate was then sintered and bonded at 300°C, 10 MPa, and 2.5 minutes.

[0292] The laminated body after the sintering process was evaluated for bonding conditions at the interface between the Cu substrate and the sintered bonding layer and at the interface between the Si chip and the sintered bonding layer based on ultrasonic flaw detection images.

[0293] Device: FineSAT200, manufactured by HITACHIPOWER SOLUTIONS

[0294] Probe: PQ2-50-13 (reflection mode)

[0295] Number of measurement points: 600 x 600 (square area with a side of 21 mm)

[0296] Judgment standard: (Good) The entire joint area has a uniform color tone.

[0297] (Poor) A portion with weak ultrasonic reflection of 10% or more in area was observed in the bonding area.

[0298] The results of the uniformity evaluation of the adhesion layer are shown in the following figure. Figure 5 .exist Figure 5 Among them, the results of Example 1 and Comparative Example 1 are selected and shown.

[0299] As can be understood from the above evaluation results, the adhesive layer of the heating bonding sheet of each embodiment contains sintered particles, and two peaks are observed on the large particle side and the small particle side in the particle size distribution measurement of the sintered particles. Therefore, the organic binder has good dispersibility and good uniformity inside the layer.

[0300] On the other hand, the adhesion layer of the comparative example contained sinterable particles in which one peak was observed in the particle size distribution measurement. Therefore, the dispersibility of the organic binder was not necessarily good, and the uniformity within the layer was low.

[0301] <Peel Test on Adhesive Layer of Wafer (Evaluation of Adhesiveness of Adhesive Layer)>

[0302] Each heating bonding sheet having only a sintered precursor layer and a bonding layer was cut to produce a test sample of 10 mm × 100 mm in size. The test sample was pasted on a Si wafer (diameter 150 mm, thickness 550 μm) plated with Ti (0.1 μm thick) / Ag (0.75 μm thick), heated on a hot plate at 70°C and rolled a 2 kg roller back and forth once, thereby pressing the test sample to the Si wafer. It should be noted that each heating bonding sheet was pressed onto the Si wafer in such a way that the Si wafer was in contact with the bonding layer. After pressing, it was placed at room temperature for 30 minutes. Using a TENSILON testing machine, the test sample was peeled off from the Si wafer in a 180-degree direction at a tensile speed of 300 mm / min. The adhesive force during peeling was measured. The results are shown in Tables 1 and 2, respectively.

[0303] As can be understood from the evaluation results of the above-mentioned adhesion evaluation, good adhesion to the wafer is achieved by setting the ratio of the first silver particles to the second silver particles in the adhesion layer within a specific range, and setting the ratio of the second silver particles to the total amount of the first silver particles and the second silver particles within a specific range.

[0304] Industrial applicability

[0305] The thermal bonding sheet of the present application can be suitably used as an auxiliary tool in manufacturing semiconductor devices, for example.

Claims

1. A sheet for thermal bonding, comprising: a sintering precursor layer containing sinterable particles; and an adhesive layer superimposed on one surface of the sintering precursor layer. The adhesion layer contains an organic binder and sinterable particles, and the content of the sinterable particles in the adhesion layer is 5% by volume or more and 40% by volume or less. When the particle size distribution of the sinterable particles contained in the adhesion layer is measured, the particle size distribution has at least two peaks.

2. The thermal bonding sheet according to claim 1, wherein The volume content of the sinterable particles in the sintering precursor layer is higher than the volume content of the sinterable particles in the adhesion layer.

3. The sheet for thermal bonding according to claim 1 or 2, wherein The sintering precursor layer contains 30 volume % or more and 70 volume % or less of the sinterable particles.

4. The sheet for thermal bonding according to claim 1 or 2, wherein The adhesion layer contains 15 volume % or more and 35 volume % or less of the sinterable particles.

5. The sheet for thermal bonding according to claim 1 or 2, wherein When the peak located on the large particle side between the highest peak and the second highest peak in the particle size distribution is defined as the peak of the large particle group of the sinterable particles, Among the sinterable particles contained in the adhesion layer, the proportion of the sinterable particles of the large particle group is 5% or more and 30% or less based on volume %.

6. The sheet for thermal bonding according to claim 1 or 2, wherein The sintering precursor layer and the adhesion layer both contain a thermally decomposable binder as an organic binder.

7. The sheet for thermal bonding according to claim 1 or 2, wherein The thickness of the sintering precursor layer is 5 μm or more and 100 μm or less, and the thickness of the adhesion layer is 2 μm or more and 20 μm or less.

8. A thermal bonding sheet with a dicing tape, comprising the thermal bonding sheet according to any one of claims 1 to 7 and a dicing tape superimposed on one surface of the thermal bonding sheet. The sintering precursor layer of the thermal bonding sheet is arranged between the adhesion layer and the dicing tape.

9. The thermal bonding sheet with a dicing tape according to claim 8, wherein The thermal bonding sheet further comprises a component migration prevention layer. The component migration prevention layer is arranged between the sintering precursor layer and the dicing tape.

Citation Information

Patent Citations

  • Heat bonding sheet, and dicing tape-attached heat bonding sheet

    JP2018037548A

  • Temperature adjustment device and controller

    JP2024023094A